Thermal and Mechanical Characteristics of Cotton Knitted Fabric Made of Non-twisted Hollow Yarn for Inner Wear (Journal of Fiber Bioengineering and Informatics, 2020)
The characteristics of a weft knitted fabric made of new cotton non-twisted hollow yarn targeting an innerwear product were investigated. The weight, thickness, thermal characteristics, tensile, shear properties,bending properties and surface properties of the knitted fabric and four commercially available inner wearfabrics were measured using a KES-FB system. The measured properties were examined to examine theusefulness of the new fabric for inner wear. Fabric characteristics were compared in a multiple comparisontest. The knitted fabric made of non-twisted hollow yarn is lighter and fuller than commercially availableinner wear fabrics. The shear stiffness and bending rigidities of the knitted fabric were similar or lowerthan ones of commercially available cotton inner wear fabrics. The surface properties of the new fabricwere similar to ones of commercially available inner wear fabrics. The fabric also has a lower Q-maxvalue (the peak value of heat transferred), lower thermal conductivity, and higher heat retention rateand is therefore warmer than the commercially available fabrics. It is thus considered that knitted fabricmade of new cotton non-twisted hollow yarn is suitable for inner wear.
Keywords: Weft Knitted Fabric; Non-twisted Hollow Yarn; Inner Wear; Thermal Properties.